1986
DOI: 10.1121/1.394323
|View full text |Cite
|
Sign up to set email alerts
|

Consonant recognition in quiet and in noise with aging among normal hearing listeners

Abstract: Consonant recognition in quiet and in noise was investigated as a function of age for essentially normal hearing listeners 21-68 years old, using the nonsense syllable test (NST) [Resnick et al., J. Acoust. Soc. Am. Suppl. 1 58, S114 (1975)]. The subjects audited the materials in quiet and at S/N ratios of +10 and +5 dB at their most comfortable listening levels (MCLs). The MCLs approximated conversational speech levels and were not significantly different between the age groups. The effects of age group, S/N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
36
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 40 publications
11
36
0
Order By: Relevance
“…Thus, our results replicate and extend the results of Gelfand et al, who found that aging produced a deterioration in consonant identification [15]. Aging significantly impaired consonant identification independent of age-related changes in audiometric thresholds, as in previous studies [4].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Thus, our results replicate and extend the results of Gelfand et al, who found that aging produced a deterioration in consonant identification [15]. Aging significantly impaired consonant identification independent of age-related changes in audiometric thresholds, as in previous studies [4].…”
Section: Discussionsupporting
confidence: 81%
“…Confusion matrices for YNH subjects can be found in Woods et al [17]. Consistent with Gelfand et al's [15] observations, we found that consonant confusions were generally similar in the ONH and YNH groups. Table 2.…”
Section: Consonant Confusionssupporting
confidence: 81%
See 2 more Smart Citations
“…In the past several decades, many studies on speech perception in noise have been conducted to examine the effects of noise on speech recognition (Gelfand, 1986;Leek et al, 1987;Parikh and Loizou, 2005). Speech recognition generally declines in conditions wherein background interference is present.…”
Section: Introductionmentioning
confidence: 99%